Manajemen Pembelajaran Al-Qur’an di RA Al-Akhyar Jakarta Selatan - Azzahro, Fatimah; Salama, Hartini (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Al-Qur’an education for young children is important, especially for the development of children’s character. This research focuses on Al-Qur’an learning management at RA Al Akhyar, Cilandak, South Jakarta. The employed method is qualitative. The research data is interviewing results with the school principal as primary source data, supplemented by observations of the Al-Qur’an learning management at RA Al-Akhyar during 2022/23 academic years in March to May 2023. The research results show Al-Qur’an learning management at RA Al Akhyar is conducted systematically, involving teachers as implementers and the teacher council in policy-making. The curriculum at RA Al Akhyar is dynamic. Planning involves the modification of self-learning models through: (1) the use of storytelling methods, (2) teachers as role models to instill Al-Qur’an knowledge and values. The learning is conducted in an effective 30-minute duration and implements the planned learning model. The learning process also involves parents in activities that require guidance. Learning evaluation is conducted systematically with daily and end-of-semester records of learning. The final assessment takes into consideration not only the child's abilities but also the child's mental maturity in Quranic learning.